2022
DOI: 10.1002/pen.26118
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of carboxylated cellulose nanofibers/monomer casting nylon composites

Abstract: Polyisocyanate was used to chemically functionalize carboxylated cellulose nanofibers (CNF-C). Composites of CNF-C/ monomer casting nylon (MC nylon) and modified CNF-C/MC nylon were fabricated by anionic ring-opening polymerization. The mechanical characteristics of the MC nylon composites and the dispersion of the CNF-C in the MC nylon were studied. The tensile strength and impact strength of composites were first increased with CNF-C addition, but then decreased as further CNF-C was added. The composites had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…[4,5,[120][121][122][123] Cellulose based fibers consist excellent aspect ratio, good strength also their size is nanoscale label with vast surface area. [124][125][126] Table 2 shows the chemical composition of numerous NFs. Figure 3 shows different chemical structures of NFs.…”
Section: Chemical Composition Of Nfsmentioning
confidence: 99%
“…[4,5,[120][121][122][123] Cellulose based fibers consist excellent aspect ratio, good strength also their size is nanoscale label with vast surface area. [124][125][126] Table 2 shows the chemical composition of numerous NFs. Figure 3 shows different chemical structures of NFs.…”
Section: Chemical Composition Of Nfsmentioning
confidence: 99%
“…Surface porosity, material polarity, biocompatibility, nontoxicity, electrical conductivity, and other excellent properties have attracted close attention from researchers. , It was also observed that there is a growing demand for comprehensive research on this material. However, the low solubility of cellulose in weakly polar solvents due to its hydroxyl-rich surface and strong hydrophilic properties has hampered the field of polymeric material compounding, as evidenced by the self-agglomeration and poor solubility of the material in the solvation system. , This defect is a critical reason for limiting its application scope. However, this problem should be considered: researchers found that CNC can be treated with an oxidized surface (increased functional groups), thus improving its solubility and dispersion in the system …”
Section: Introductionmentioning
confidence: 99%
“…However, the low solubility of cellulose in weakly polar solvents due to its hydroxyl-rich surface and strong hydrophilic properties has hampered the field of polymeric material compounding, as evidenced by the self-agglomeration and poor solubility of the material in the solvation system. 19 , 20 This defect is a critical reason for limiting its application scope. However, this problem should be considered: researchers found that CNC can be treated with an oxidized surface (increased functional groups), thus improving its solubility and dispersion in the system.…”
Section: Introductionmentioning
confidence: 99%
“…Nanocellulose extracted from natural cellulose is regarded as an emerging green nanomaterial . Due to its salient properties, including high crystallinity and specific surface area, it has the potential to enhance the compressive strength of composite materials and reduce their brittleness while simultaneously increasing their toughness. , It has high potential for applications across diverse fields, including drug carriers, , hydrogels, and adhesives, among others. Cellulose can be oxidized to produce dialdehyde cellulose. This dialdehyde cellulose has the ability to form dynamic imine bonds with amino-containing polymers through Schiff base reactions.…”
Section: Introductionmentioning
confidence: 99%